Comparative Analysis of the Use of Ant and Alum Freezers on the Income of Rubber Farmers in Lubuk Raja District, South OKU Regency - Feliza, M; Oktarina, Y; Efrianti, R; Sari, Fifian Permata (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Rubber farmers in Indonesia make lump slabs with ant acid and some still use freezing materials that can damage the quality of rubber such as alum. Besides causing damage to the quality of the rubber, it also causes a bad smell which is very disturbing to the people around the place where the latex is processed. The pungent foul odor is caused by bacteria which biodegrade proteins into ammonia and sulfide compounds. OKU Regency is the fifth largest district in the area of ??rubber plantations in South Sumatra Province. Based on land suitability, plantations are a potential sector to be developed with the superior commodity rubber. The smallholder plantation sector with rubber is the leading commodity in the Ogan Komering Ulu Regency area. This research will be carried out in Lubuk Raja District, OKU Regency. The location determination was carried out purposively considering that Lubuk Raja District, OKU Regency, is one of the rubber producing areas in South Sumatra, especially OKU. The research method used in this research is the survey method. The sampling method used in the research is to answer the formulation of the big problem of rubber farmer income in Lubuk Raja District using income analysis and comparative analysis. Based on the analysis of the results of the research that has been carried out, it can be concluded that the average income of farmers who use ant acid per hectare per month is IDR 5,093,515.15/ha/month. Meanwhile, the average income of rubber farmers who use alum freezers is higher than the income of farmers using ant acid freezers, namely IDR 20,234,572.46/ha/month. Based on the Independent Sample t-Test in the Equal Variances Assumed section, the sig value (2-tailed) is 0.04 < 0.05 (95% confidence level). So it is concluded that H1 is accepted and H0 is rejected, which means there is a difference in the income of lump rubber farmers who use ant acid and alum freezers.